Development of an Augmented Reality Book Based on Science Inquiry for Early Childhood - Siswono, Hendrik; Zahro, Ianatuz; Cahyono, Arie Eko (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to develop an Augmented Reality (AR)-based learning medium using a Science Inquiry approach to enhance science literacy among early childhood learners. The study follows the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects included early childhood students and teachers from two preschools in Jember, Indonesia. Research instruments involved observations, questionnaires, and interviews to assess children's understanding, engagement, and motivation, as well as teacher satisfaction and ease of use. Data analysis techniques included both formative and summative evaluations: formative evaluation examined each stage of the ADDIE model, while summative evaluation assessed the AR medium's effectiveness in enhancing science literacy and overall learning experience. Trial results show that the use of AR significantly improves children's understanding of scientific concepts, active engagement, and motivation in learning science. Additionally, both children and teachers rated the AR media as easy to use, with high levels of satisfaction reported by teachers, underscoring the medium’s accessibility and impact. Summative evaluations reveal that the AR medium positively impacts science literacy, with an overall rating of "excellent." Consequently, AR-based media with a Science Inquiry approach shows great promise as an innovative solution for improving science literacy among young children in Indonesia.